2022
DOI: 10.1111/tops.12605
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences and Skill Training in Cognitive Mapping: How and Why People Differ

Abstract: Spatial ability plays important roles in academic learning and everyday activities. A type of spatial thinking that is of particular significance to people's daily lives is cognitive mapping, that is, the process of acquiring, representing, and using knowledge about spatial environments. However, the skill of cognitive mapping shows large individual differences, and the task of spatial orientation and navigation poses great difficulty for some people. In this article, I look at the motivation and findings in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 113 publications
1
11
0
Order By: Relevance
“…Spatial knowledge gained from navigation has mostly been measured by testing only some of these various domains of knowledge, however, and more information is needed about the relationship between them (van der Ham et al, 2020 ; Muffato et al, 2022 ). Various human factors, such as visuospatial abilities and wayfinding inclinations, have been found to support environmental knowledge (Ishikawa, 2022 ; Meneghetti et al, 2021 ), but how they relate to the different types of environmental knowledge gained after passively learning a VE has yet to be investigated. Learning from passive navigation may result in reduced environmental knowledge (Chrastil & Warren, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial knowledge gained from navigation has mostly been measured by testing only some of these various domains of knowledge, however, and more information is needed about the relationship between them (van der Ham et al, 2020 ; Muffato et al, 2022 ). Various human factors, such as visuospatial abilities and wayfinding inclinations, have been found to support environmental knowledge (Ishikawa, 2022 ; Meneghetti et al, 2021 ), but how they relate to the different types of environmental knowledge gained after passively learning a VE has yet to be investigated. Learning from passive navigation may result in reduced environmental knowledge (Chrastil & Warren, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Visuospatial factors play a part in spatial learning (He et al, 2021 ; Hegarty et al, 2006 ; Ishikawa, 2022 ; Weisberg, et al, 2014 ). The term visuospatial factor covers a broad and heterogeneous set of aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Surveys were selected to (a) understand effects of participants’ traits/characteristics and (b) possibly include as covariates to gain a deeper of understanding of the effects of traits and characteristics. Work by Ishikawa (2023), Ishikawa & Montello (2006), and Weisberg & Newcombe (2018) indicates that individuals with a keener sense of direction may perform better on tasks such as aviation that require an accurate configurational understanding of the environment. Therefore, we incorporated the Santa Barbara Sense of Direction (SBSOD) scale.…”
Section: Methodsmentioning
confidence: 99%
“…Cognitive maps can be acquired through verbal or text-based descriptions of routes or environments and the spatial mental models developed from text may resemble the cognitive maps developed during navigation (Brunye et al, 2007 ; Giudice et al, 2007 ; Picucci et al, 2013 ; Taylor & Tversky, 1992 ). Importantly, research has indicated that people generally navigate more efficiently and effectively when given external supports like maps and verbal directions than when navigating without these tools (Hund & Minarik, 2006 ; Ishikawa et al, 2008 ; Krukar et al, 2020 ; Lowen et al, 2019 ; Munzer et al, 2020 ; Saucier et al, 2002 ). Yet, despite their usefulness in aiding navigation behavior while they are available, such external supports may be less useful in helping people build spatial knowledge.…”
Section: Introductionmentioning
confidence: 99%